Providing systematic detailed information on medication upon hospital discharge as an important step towards improved transitional care. (18th February 2014) - Hohmann, C.; Neumann‐Haefelin, T.; Klotz, J. M.; Freidank, A.; Radziwill, R.
Summary What is known and objective Good communication between hospital and primary care physicians (PCPs) is important for the continuity of patient care in the transition phase following hospital treatment. Drug‐related problems and medication errors may occur at that interface. Discharge letters often lack a structured medication report at the end and therefore may not provide the reasons for medication changes, resulting in low adherence rates. The objectives were to develop a structured medication report as part of the discharge letter, to evaluate the impact of the medication report in ischaemic stroke patients and to identify the most important issues in the transitional care process of stroke patients. Methods First, a structured medication report was developed. Thereafter, the impact of this new medication report on clinical practice was evaluated with an open, prospective, interventional two‐phase study conducted at the Klinikum Fulda gAG (Germany), which included patients with ischaemic stroke and >2 drugs in the discharge medication. In the control group (CG), the neurologist included the current medication in the discharge letter. In the intervention group (IG), the clinical pharmacist added the detailed information to a medication report. To evaluate adherence to discharge medication, the PCP was interviewed 3 months after hospital discharge about the medication. Adherence was measured with respect to the entire medication regimen, antithrombotic and cholesterol‐lowering drugs and discontinued medication. The most important issues in the transitional care for patients with ischaemic stroke were identified on the basis of the secondary stroke prevention and cardiovascular risk factors. Results and discussion Overall, 312 patients were enrolled in the study with 156 patients in each group. By providing detailed information in the newly developed discharge letter, adherence increased significantly from 83·3% (CG) to 90·9% (IG; P = 0·01). Significant differences between the CG and IG were found with regard to adherence to both antithrombotic drugs [83·8% CG vs. 91·9% IG (P = 0·033)] and statin therapy [69·8% CG vs. 87·7% IG (P < 0·001)]. What is new and conclusion The use of a structured medication report as part of the discharge letter leads to improved adherence to hospital discharge medication.